Effects of pre-cooling procedures on intermittent-sprint exercise performance in warm conditions - Duffield, R.; Marino, F. E. (European Journal of Applied Physiology, 2007)
The aim of this study was to determine whether pre-cooling procedures improve both maximal sprint and sub-maximal work during intermittent-sprint exercise. Nine male rugby players performed a familiarisation session and three testing sessions of a 2× 30-min intermittent sprint protocol, which consisted of a 15-m sprint every min separated by free-paced hard-running, jogging and walking in 32°C and 30% humidity. The three sessions included a control condition, Ice-vest condition and Ice-bath/Ice-vest condition, with respective cooling interventions imposed for 15-min pre-exercise and 10-min at half-time. Performance measures of sprint time and % decline and distance covered during sub-maximal exercise were recorded, while physiological measures of core temperature (T core), mean skin temperature (T skin), heart rate, heat storage, nude mass, rate of perceived exertion, rate of thermal comfort and capillary blood measures of lactate [La-], pH, Sodium (Na+) and Potassium (K+) were recorded. Results for exercise performance indicated no significant differences between conditions for the time or % decline in 15-m sprint efforts or the distance covered during sub-maximal work bouts; however, large effect size data indicated a greater distance covered during hard running following Ice-bath cooling. Further, lowered T core, T skin, heart rate, sweat loss and thermal comfort following Ice-bath cooling than Ice-vest or Control conditions were present, with no differences present in capillary blood measures of [La-], pH, K+ or Na+. As such, the ergogenic benefits of effective pre-cooling procedures in warm conditions for team-sports may be predominantly evident during sub-maximal bouts of exercise.